Investigation of the Possible Correlation between Idiopathic Parkinson’s Disease and Diabetes Mellitus in Egyptian Patients: A Pilot Study - Afnan AwadAllah Elgnainy; Mohammad Ismail Hamed; Wael Osman Mohamed; Nagwa Ali Sabri (Neurology Research International)
Objectives. To study the diabetes-Parkinson's disease (PD) linkage. Methods. The investigators recorded the rapid eye movement sleep behavior disorder screening questionnaire (RBDSQ) score for 60 diabetic patients: 30 patients were treated with metformin-inclusive sulfonylurea and 30 patients were treated with sulphonylurea(s) monotherapy and matched with 30 controls. We evaluated blood glucose kinetics during a 75 g oral glucose tolerance test for (22) nondiabetic parkinsonian patients and (10) controls. The motor complications scores were recorded for all parkinsonian patients using the relevant parts of the Unified Parkinson’s Disease Rating Scale (UPDRS) part IV. Results. Diabetics recorded higher scores of RBDSQ than controls (p<0.001), with no differences related to antidiabetic therapy. In nondiabetic PD patients, after oral glucose, blood glucose was significantly higher at T1 (p<0.001) than controls. Moreover, the total area under the time curve for blood glucose levels was significantly higher in PD compared to controls (281.22 ± 52.25 vs. 245.65 ± 48.63 mg.hr./dL; p=0.013). Higher blood glucose levels were associated with motor abnormalities. Diabetic PD patients recorded higher scores of UPDRS (p<0.001). Conclusion. Diabetes mellitus and Parkinson’s disease are linked, which raises concerns about either of them, probably increasing the risk of the other. This trial is registered with NCT03685357.